Aggregate Stock Market Illiquidity and Bond Risk Premia - Kees E. Bouwman; Elvira Sojli; Wing Wah Tham (Tinbergen Institute, 2012)
We assess the effect of aggregate stock market illiquidity on U.S. Treasury bond risk premia. We find that the stock market illiquidity variable adds to the well established Cochrane-Piazzesi and Ludvigson-Ng factors. It explains 10%, 9%, 7%, and 7% of the one-year-ahead variation in the excess return for two-, three-, four-, and five-year bonds respectively and increases the adjusted R2 by 3-6% across all maturities over Cochrane and Piazzesi (2005) and Ludvigson and Ng (2009) factors. The effects are highly statistically and economically significant both in and out of sample. We find that our result is robust to and is not driven by information from open interest in the futures market, long-run inflation expectations, dispersion in beliefs, and funding liquidity. We argue that stock market illiquidity is a timely variable that is related to right-to-quality episodes and might contain information about expected future business conditions through funding liquidity and investment channels.
urn:NBN:nl:ui:15-1765/38216
Keywords: G10; G20; G14; 330; Market liquidity; Bond risk premia; Flight-to-quality; Risikoprämie; Zinsstruktur; Anleihe; Marktliquidität; Prognose